Constructivism and international relations : Alexander Wendt and his critics / edited by Stefano Guzzini and Anna Leander. - Guzzini, Stefano; Leander, Anna (The new international relations, 2006)
Summary: This volume addresses both Alexander Wendt's social theory and international relations theory, exploring a variety of constructivist debates without reducing constructivism to one single position